A Traumatic Intrusion with Transgressive Possibilities: power as a relational and discursive phoneomenon - McCarthy, Imelda (Murmurations: Journal of Transformative Systemic Practice, 2018)
Therapy in one way or other has always been about subversion - whether it was the undermining of symptoms, the provision of a transitional space for the considering of serious changes in one’s life, a space for political conversations with social ramifications or more recently the co-creation of a space where the transformation of consciousness might take place. All of these aspects of therapy are about disrupting the habitual, the unseen and the conditioned in our personal and social lives. As such, one could posit that therapy, to be true to its spirit, is transgressive of the taken for granted - those conditioned responses which both keep us going and challenge us to transform. In that way, all change is in part a transgressive act. In our moves to evolve or co-evolve there needs to be a going beyond a previous positioning (Simon 2007). This special issue is a celebration of such an evolution and transgressions by many courageous beings in their own small and larger ways of living out a life of difference on the margins. Indeed this marginal siting cannot be but transgressive as they illuminate that which marginalises in the first place. This paper also relates to a transgression of a small kind. For many years I had worked with metaphors and experiences of marginalisation, power, gender inequality, abuse and victimisation. These categories seemed quite clear until the intrusion that is described here entered my life and home. What follows is my attempt at deconstructing previous clarities and restorying a lived experience of ambiguities in relation to power and powerlessness. I will explore a power saturated and personally traumatic event as a relational enactment. I have chosen to explicate my own experiences this time as for most presentations and papers, I speak as a professional working with clients who have experienced trauma. However, on this occasion I thought I would take a reverse position and address my own trauma which I first wrote about (for myself) in the immediate aftermath of the event described.